THU0337 Worse Disease Trajectory in Early RA Patients is Associated with Lower Improvements in Health Related Quality of Life; Results from a Multicenter Early RA Cohort. (9th June 2015) - Barnabe, C.; Bartlett, S.J.; Sun, Y.; Boire, G.; Hitchon, C.A.; Keystone, E.; Haraoui, B.; Thorne, J.C.; Tin, D.; Pope, J.; Bykerk, V.P.
Abstract : Background: High variability in disease trajectories in early RA (ERA) in settings of usual care has many patients experiencing long delays in, or not even achieving, low disease activity or remission. These trajectories should relate to anticipated improvements in Health-Related Quality of Life (HRQoL), and vary by accumulated radiographic damage. Objectives: To determine if the magnitude of improvements in HRQoL vary in heterogeneous disease trajectories and by radiographic progression. Methods: Cluster-based trajectory modeling identified 5 mutually exclusive ERA disease activity trajectories by posterior membership probability using DAS28 over 24 months. Subjects from CATCH (Canadian Early Arthritis Cohort) who completed Veteran's RAND 12 Forms (VF12) annually and fatigue intensity every 3-6 months were included in this analysis. Baseline values and mean changes in the VF12 mental and physical component scores (MCS, PCS) and fatigue intensity in the past week (0-10 scale) were examined for differences by trajectory group, and by significant radiographic progression (ΔvdH-TSS >3.5) in the subset with serial x-rays (n=488). Analysis of Covariance (ANCOVA) was used to test for differences between trajectory groups and radiographic progression status, with adjustment for covariates (age, sex, number of comorbidities, low income, smoking, race). Results: The analysis includes eligible1586 patients (mean 54 years, 181 days of symptoms, 73% female, 82% Caucasian, 18% smokers, 70% seropositive). Half (50%) begin in high disease activity state (DAS), of which only 20% rapidly reach remission (Group 1) (Figure-A ). Heterogeneous baseline scores and change in PCS (Fig-B ), MCS (Fig-C ) and Fatigue (Fig-D ) scores were observed between trajectory groups in the first 12 months, with all scores plateauing from months 12-24. Group 1, Group 4 (begins in high DAS, achieves low DAS by 24 months) and Group 5 (begins in high DAS, achieves moderate DAS by 24 months) have the worst baseline mean PCS score, with Group 1 improving by a mean of 16.4 units compared to 9.9 units in Group 4 and 3.8 units in Group 5 in the first 12 months (between group differences p<0.001). Group 1 also has the greatest improvement in mean MCS (mean 9.7 units vs Group 4 5.5 units, and Groups 2, 3 and 5 improving by 2.3-3.6 units; between group differences p<0.001). Group 1 also has the greatest improvement in Fatigue over 12 months (-4.1 units vs -1.0 to -2.3 in other groups; between group differences p<0.001). No significant differences in rates of improvement in HRQoL measures were seen when comparing subjects with significant radiographic progression compared to those who did not. Conclusions: Disease trajectory independent of sociodemographic covariates impacts the magnitude and rate of change in HRQoL measures. This effect is not dependent on radiographic progression. These data support the need to achieve disease targets in a timely fashion to ensure optimal improvements in HRQoL measures in ERA. Disclosure of Interest: C. Barnabe: None declared, S. Bartlett: None declared, Y. Sun: None declared, G. Boire: None declared, C. Hitchon: None declared, E. Keystone: None declared, B. Haraoui: None declared, J. C. Thorne: None declared, D. Tin: None declared, J. Pope: None declared, V. Bykerk Grant/research support from: The CATCH study was designed and implemented by the investigators and financially supported initially by Amgen Canada Inc. and Pfizer Canada Inc. via an unrestricted research grant since the inception of CATCH. As of 2011, further support was provided by Hoffmann-LaRoche Ltd., UCB Canada Inc., Bristol-Myers Squibb Canada Co., AbbVie Corporation (formerly Abbott Laboratories Ltd.), and Janssen Biotech Inc. (a wholly owned subsidiary of Johnson & Johnson Inc.)